CDKN2B Methylation and Aortic Arch Calcification in Patients with Ischemic Stroke - Zhou, Shuyu (J Atheroscler Thromb, 2017)
Aim: CDKN2A/2B near chromosome 9p21 has been proposed as a potential genetic etiology for both atherosclerosis and arterial calcification. DNA methylation, which can change the expression of CDKN2A/2B, may be an underlying mechanism for this association. This study aimed to evaluate whether CDKN2A/2B methylation is related to aortic arch calcification (AAC) in patients with ischemic stroke. Methods: DNA methylation levels of CDKN2A/2B was measured using venous blood samples in 322 patients with ischemic stroke. A total of 36 CpG sites around promoter regions of CDKN2A/2B were examined. AAC was quantified with Agatston score based on results of computed tomography angiography. Results: There were 248 (77.0%) patients with and 74 (23.0%) patients without evident AAC. Compared with patients without AAC, patients with AAC had higher methylation levels of CDKN2B (5.72 vs 4.94, P < 0.001). Using a generalized linear model, positive correlation between methylation levels and log-transformed calcification scores was detected at CDKN2B (β = 0.275 ± 0.116, P = 0.018). Conclusion: Patients with higher levels of DNA methylation of CDKN2B may bear increased risk for AAC. Further studies to reveal the underlying mechanisms of this association are warranted for establishing a cause–effect relationship.